Marginal support for a trophic cascade among sympatric canids in peripheral wolf range. Issue 11 (20th August 2021) - Fowler, Nicholas L.; Kautz, Todd M.; Petroelje, Tyler R.; Wilton, Clay M.; Kellner, Kenneth F.; O'Brien, Daniel J.; Parsons, Bill; Beyer, Dean E.; Belant, Jerrold L.
Abstract: Trophic cascades reportedly structure ecological communities through indirect species interactions. Though the predator–herbivore–autotroph relationship has received much attention, mechanistic evidence supporting intraguild trophic cascades is rare. We established 348 remote camera sites (1 August–5 September 2019) across seven study areas of varying wolf ( Canis lupus ) density including one study area where wolves were absent in northern Michigan, USA. Using multi‐species occupancy modeling at species‐relevant spatial scales, we evaluated the hypothesis that increased wolf occurrence suppresses coyote ( C . latrans ) occurrence with corresponding increased red fox ( Vulpes vulpes ) occurrence mediated by land cover edge density, human presence, and temporal partitioning. Remote cameras recorded >600, 000 images and included 6, 370, 10, 137, and 4, 876 detections of wolves, coyotes, and foxes, respectively. Fox occupancy probability was more than three times as high (0.29) at camera sites where wolves were present, relative to sites wolves were absent (0.09). Pairwise species interactions supported expected size‐based dominance patterns among canids and insignificant effects were directionally consistent with reported reduced strength of top‐down effects in peripheral wolf range. Increased edge density also increased co‐occurrence of coyote and wolves, likely a function of increased prey availability and refugia for coyotes. Though foxes occurred in spatial proximity to wolves, competition was limited by greater temporal partitioning than observed between coyotes and foxes that were spatially segregated. Collectively, our results provide marginal support for the reported trophic cascade among wolves, coyotes, and foxes wherein top‐down effects may be reduced near the edge of current wolf distributions. As predators continue to recolonize portions of their historic range, knowledge of the effects on intraguild predators has implications for species management and predicting prey population responses.